Deformation modulus tested by the falling ball test method and the experimental verification. Issue 1 (February 2021) - Xue, Yingqi; Han, Xiaokun; He, Huayang; Luo, Zhu
Abstract: In filling engineering, the mechanical properties of geomaterials are the most important mechanical indicators. With the improvement of the measurement technology, the falling ball test (FBT) method has been gradually popularized and applied to the testing of geomaterials mechanical properties. In order to verify the testing accuracy of the FBT method, experimental results of the deformation modulus tested for the homogeneous fine-grained materials and the layered structures using the FBT method are compared with the K 30 plate load test, which is the earliest and the most widely used in-situ test method. And some conclusions are drawn in this present paper.